2000
DOI: 10.1046/j.1365-2745.2000.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity affects culturable soil bacteria in experimental grassland communities

Abstract: Summary1 Utilization of carbon sources by culturable soil bacteria can be assessed with BIOLOG microtiter plates (contain 31 C sources). We used this technique to investigate bacterial community structure at various levels of plant diversity. Plant diversity levels were replicated and we investigated the in¯uence of three plant functional groups, grasses, legumes and non-leguminous herbs, as well as the in¯u-ence of individual plant species. 2 Catabolic activity and catabolic diversity of culturable soil bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
155
3
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(180 citation statements)
references
References 34 publications
17
155
3
5
Order By: Relevance
“…Thus, the decrease of plant richness under exclosure could impact the carbon inputs by affecting the aboveground biomass in the community. Besides, several investigators demonstrated that the increased plant richness could affect the carbon cycling in soil by increasing microbial biomass and activity (Steinbeiss et al, 2008;Wardle et al, 1999;Hooper et al, 2000;Stephan et al, 2000). In addition, the decrease of legumes abundance in the fence meadow could decrease soil C sequestration as suggested by Fornara and Tilman (2008).…”
Section: Effect Of Exclosure On 13 C Dynamic and Allocationmentioning
confidence: 99%
“…Thus, the decrease of plant richness under exclosure could impact the carbon inputs by affecting the aboveground biomass in the community. Besides, several investigators demonstrated that the increased plant richness could affect the carbon cycling in soil by increasing microbial biomass and activity (Steinbeiss et al, 2008;Wardle et al, 1999;Hooper et al, 2000;Stephan et al, 2000). In addition, the decrease of legumes abundance in the fence meadow could decrease soil C sequestration as suggested by Fornara and Tilman (2008).…”
Section: Effect Of Exclosure On 13 C Dynamic and Allocationmentioning
confidence: 99%
“…Although the outcomes reflected only patterns of carbon source utilization during the Ecoplate incubation period and only select metabolic functions were represented in the Ecoplates (Preston-Mafham et al 2002;Zheng et al 2005), CLPPs provide a fast and sensitive way to equally compare functional characteristics of soil microbial communities. Moreover, functional diversity can provide a minimum estimate of taxonomic diversity (Stephan et al 2000). In this study, cumulative averaged metabolic activity of soil microbial communities demonstrated a quadratic change with Eucalyptus plantation stand age (see Fig.…”
Section: Discussionmentioning
confidence: 50%
“…However, actual observations showed positive (Stephan et al 2000;Zak et al 2003;Eisenhauer et al 2011;Lange et al 2015), negative or no response (Johnson et al 2008) of soil microbial biomass, activity and diversity to increasing plant diversity (Zhang et al 2010;Rottstock et al 2014). Soil micro-organisms are mostly heterotrophic; thus, they decompose plant material for food or use plant exudates (LorangerMerciris et al 2006).…”
Section: Introductionmentioning
confidence: 99%